PENGARUH METODE FONIK TERHADAP KETERAMPILAN MEMBACA PERMULAAN ANAK TUNARUNGU KELAS I DI SDLB-B - Ardilistiana P, Mega (Jurnal Pendidikan Khusus, 2017)
Abstract: Deafness leads to inhibition of language skills, which include listening skills, speaking skills, reading skills, and writing skills. To develop these skills, deaf children need to understand how to master reading and speaking skills. The reading skill needs to be controlled by the deaf children because to add language and to understand long and related sentences. So this study aims to determine the effect of the Fonik method on reading skills of children with hearing impairment. This research uses quantitative approach, with pre-experiment design with One Group Pretest-Posttest Design type. The results of data analysis showed that, the use of Fonik method significantly influence the reading skills of children with hearing impairment grade I in SDLB-B Putera Asih Kediri.   Keywords: Phonic Method, Reading, Child Deaf.